Periprocedural Bleeding Complications of Brain AVM Embolization with Onyx - Liu, L. (Centauro S.r.l., 2010)
The advent of Onyx has provided a new method for neurointerventional therapists to treat brain AVMs. Although some retrospective studies have reported complications for AVM embolization with Onyx, periprocedural bleeding complications with Onyx embolization have not yet been described in detail. The aim of this retrospective study was to analyze the factors of Onyx-related bleeding complications and to find a way to avoid and manage these complications. From January 2003, patients with AVMs recruited in our institution started to be treated by Onyx embolization. From January 2007 to July 2009, 143 consecutive interventions were performed in 126 patients using flow-independent microcatheters and Onyx as embolic agents. Seven patients encountered bleeding complications (5.4% per patients and 4.7% per procedures) during or after the endovascular procedures. Among them, five bleeding episodes occurred during procedures, the other two after procedures. Details of the seven patients' clinical presentations, imaging presentations, speculative reasons and management of these complications were recorded. Follow-up data, including postoperative course, clinical symptoms and duration of follow-up were documented. The five active bleedings discovered in procedures were managed in time, and the patients recovered without any new neurological symptoms compared with preoperation. However, of the two bleeding episodes that occurred after interventional procedures, one was detected half an hour later: the patient was remained comatose two months later after resection of right occipital hematoma; the other who encountered intraventricular and midbrain hemorrhage was treated conservatively and suffered Parinaud syndrome and hemianesthesia. Conclusion: Periprocedural bleeding of AVMs embolization is considered a severe and devastating complication. The clinical course and prognosis of bleeding mostly depends on prompt detection and management. Interventional embolization is an effective method to manage bleeding during procedures, and the detection of risk factors and imaging signs of bleeding is extremely important.